2019
DOI: 10.1177/1847980419832724
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of fiber-optic phase-gradient meta-tips for sensing applications

Abstract: Recently, within the emerging framework of "lab-on-fiber" technologies, we successfully demonstrated the integration of phase-gradient plasmonic metasurfaces on the tip of an optical fiber. The resulting optical-fiber "meta-tips" promise to empower the typical fiber-optics application scenarios (e.g. sensing, telecommunications, imaging, etc.) with the advanced light-manipulation capabilities endowed by metasurfaces. Here, we explore more in detail the possibility to exploit this platform in label-free biologi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(14 citation statements)
references
References 53 publications
0
14
0
Order By: Relevance
“…This MT configuration was applied for beam polarization and phase gradient control. 262 Similarly, Yang et al 263 reported an optical metalens patterned on the core area of a PCF endface to be used for light focusing at communications wavelengths, which showed a maximum enhanced optical intensity as large as 234% at the focal point of the lens. Moreover, Xomalis et al 264 reported a fully fiberized and packaged optical switching meta-fiber device based on coherently controlled absorption [Fig.…”
Section: D Functional Surfacesmentioning
confidence: 99%
“…This MT configuration was applied for beam polarization and phase gradient control. 262 Similarly, Yang et al 263 reported an optical metalens patterned on the core area of a PCF endface to be used for light focusing at communications wavelengths, which showed a maximum enhanced optical intensity as large as 234% at the focal point of the lens. Moreover, Xomalis et al 264 reported a fully fiberized and packaged optical switching meta-fiber device based on coherently controlled absorption [Fig.…”
Section: D Functional Surfacesmentioning
confidence: 99%
“…Numerical simulations showed that for d ≥ 1000 nm, the reflectivity spectra are mainly affected by the resonance of the single antennas and much more mildly by the array structure. [40] Step 2: Having fixed L 1 and L 2 to the values found at step 1, we gradually decrease d, up to its minimum value that allows the MS resonance wavelength to be as close as possible to (but still greater than) r SW . Indeed, as d decreases, the resonance wavelength of the MS blueshifts, so that, at the optimal value of d, the resonance wavelength lies about in the middle of the range of interest.…”
Section: Design Proceduresmentioning
confidence: 99%
“…[39] The remain-ing parameters to be optimized are the antennas' side lengths, L 1 and L 2 , and the distance d between neighboring elements. Based on a preliminary numerical study, [40] these parameters are tuned so that, at the resonance wavelength r , the grazing condition is satisfied both in transmission and in reflection; this implies that at r , the (constant) phase gradient must be ≥ max{n t , n r } 2 0 = n r 2 ∕ 0 . Furthermore, in order to improve the quality factor of the resonance, r must be slightly larger than r SW ; this implies the coupling of the antennas' resonance to the lattice surface modes, whose effects have been widely studied in the topical literature.…”
Section: Design Proceduresmentioning
confidence: 99%
See 1 more Smart Citation
“…The principles of operation of the device, applications along with their extraordinary advantages, fabrication challenges, and prospects are being discussed in a detailed manner. In the aspect of fabrication of new and novel optical devices, metasurface and optical fiber integrated [124,125] for the development of novel "lab-on-fiber" structures are also illustrated in this paper, which possess enormous potentials for future applications. The review work is concluded with a summarization of the challenges and prospects of this research area.…”
Section: Introductionmentioning
confidence: 99%